A new species of the spider genus Solenysa from China (Araneae, Linyphiidae) - Tian, Jiahui; Tu, Lihong (Zootaxa, 2018)
The genus Solenysa Simon, 1894 belongs to Linyphiidae Blackwall, 1859, which is a species-rich group, including 608 genera and 4,571 species (World Spider Catalog 2018). Solenysa currently includes 14 species from China, Japan and the Korean Peninsula (Simon 1894; Namkung 1986; Li & Song 1992; Gao, Zhu & Sha 1993; Tu, Ono & Li 2007; Ono 2011; Tu & Hormiga 2011; Wang, Ono & Tu 2015). The linyphiid phylogeny based on molecular data shows that Solenysa species forms one of the seven main clades within Linyphiidae (Wang et al. 2015). According to the phylogenetic analysis based on morphological data, Tu and Hormiga (2011) divided the genus Solenysa into four species groups, each having a unique genital type comprised by series genital characters. As an old branch with a long evolutionary history, Solenysa spiders have accumulated a long list of synapomorphies (Tu & Hormiga 2011), not only having a unique somatic appearance, but also specific genitalic characters that distinguish them from all other linyphiids.